Comparative Effects of Epidural Analgesia and Intramuscular Morphine on Maternal and Neonatal Outcomes: A Retrospective Cohort Study - Abdelrahman Elsayed (6288913) (2023)
Background The global practice of pain management during labor involves the use of Epidural Analgesia (EA) or intramuscular (IM) morphine. However, the impact of these methods on maternal and neonatal short-term outcomes remains unclear. Objective Our primary research goal is to examine the effect of labor exposure to EA and/or IM morphine on the likelihood of Neonatal Intensive Care Unit (NICU) admission. Secondary objectives encompass the exploration of associated maternal and neonatal demographics and outcomes, including sepsis, respiratory distress, instrumental delivery, birth traumas, low APGAR scores, and chorioamnionitis. Methods We conducted a retrospective cohort study of 7325 women who underwent low-risk normal vaginal deliveries at the Women’s Wellness and Research Center (WWRC), previously known as the Women’s Hospital, in Qatar from January 2017 to April 2018. The mothers were categorized based on the pain management regimen received during active labor, and maternal and neonatal short-term outcomes were examined across these groups using descriptive and logistic regression analysis. Results Of the sample, 2606 women received EA, 1338 received IM morphine, 286 received both, and 3304 received neither. Multinomial regression analysis revealed no differences in NICU admissions between groups. Qatari women were more likely to receive EA (aOR 1.87, 95%CI 1.18– 2.94, p=0.007). Labor induction with prostaglandin (aOR 3.94, 95%CI 1.83–8.46, p<0.001) was associated with a prolonged first stage (aOR 1.003, 95%CI 1.01–1.005, p<0.001) and second stage of labor (aOR 1.02, 95%CI 1.013–1.024, p<0.001), and less risk for postpartum hemorrhage (aOR 0.042, 95%CI 0.18 – 0.99, p=0.048). IM morphine was linked to assistive reproductive technology (aOR 9.6, 95%CI 1.013–91.4, p=0.049), and low Apgar scores at 1 minute (aOR 11.3, 95%CI 2.23–57.2, p=0.003). The combined use of EA and IM morphine was more associated with women's age (aOR 1.088, 95%CI 1.00–1.184, p=0.049), a prolonged first stage (aOR 1.02, 95%CI 1.014–1.026, p<0.001) and second stage of labor (aOR 2.09, 95%CI 1.35–3.25, p<0.001), vaginal birth after Cesarean (aOR 4.49, 95%CI 1.18–17.0, p=0.27), and labor induction (aOR 4.79, 95%CI 1.51–15.2, p=0.008). Conclusion Our study found no significant differences in NICU admissions between different labor pain management strategies. However, specific outcomes were associated with the use of EA, IM morphine, or both. Further research is needed to clarify these associations and optimize labor pain management.